The Body Metaphor Reinforcing the Identity of the In-Group in Ephesians - Vrey, Alta; Nortjé-Meyer, Lilly 1957- (2019)
Social Identity Theory is used in this article to determine the identity of the early Christians in Ephesians. The change that Christ brought to the world had radical consequences, resulting in the early Christians asking the question: Who are we? In contemporary society, the search for identity amidst the uncertainty of a changing world again highlights the question: Who are we? The author of Ephesians attempts to answer this question of identity through the metaphor of the body. According to this author, the early Christians are still children in their identity formation and have to grow up and reach adulthood, which is represented as the perfect body of an adult man. The author's attempt to strengthen the identity of the in-group and determine their actions and behaviour was successful in the case of the two sub-groups of Jewish and gentile believers. However, Jesus's equalising, liberating and reconciliatory work that promised to bring unity and equality failed to reach the gender sub-groups within the Christian in-group. The author used the metaphor of the body to reinforce the unity and equality within the in-group, but the male and female sub-groups still functioned according to reigning cultural values.
Keywords: Bible. Ephesians; Ephesians; Group Identity; Social Identity Theory; Body Metaphor; Female; Gender; Identity; in-group; Male; Festschrift